THE USE OF DIGITAL TECHNOLOGIES IN SECONDARY EDUCATION AS A FACTOR IN IMPROVING THE QUALITY OF EDUCATION - Subanov Vahob (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: The article examines the role of digital technologies in modern secondary education. Attention is focused on the use of all digital technologies in secondary education. The article highlights the problems of digital technologies in secondary education, the transformation of education in the conditions of digitalization of society